Analysis and Optimization of Allianz Bussvission Marketing Strategy in Popularizing Life Insurance Products. - Andini, Bunga Putri; Nugroho, Rusdi Hidayat (Business and Investment Review, 2024)
This study discusses the optimization of marketing strategies implemented by PT Bussvision Allianz to popularize life insurance products in Indonesia. The low level of public awareness regarding the importance of insurance remains a major challenge for the insurance industry in Indonesia. Through focused marketing strategies, such as the use of digital technology, customer education, and market segmentation, Bussvision Allianz aims to enhance public understanding of the benefits of insurance. This research employs a qualitative approach, with data collected through interviews and literature studies. The results show that digital innovation, educational campaigns, and customer-oriented approaches are key to increasing life insurance market penetration. However, challenges such as negative perceptions and low financial literacy still require comprehensive solutions. With integrated and adaptive marketing strategies, PT. Bussvision Allianz has successfully created effective approaches to reach diverse market segments and build public trust in life insurance products.